Down or Out: Assessing the Welfare Costs of Household Investment Mistakes - Calvet, Laurent E.; Campbell, John Y.; Sodini, Paolo (Journal of Political Economy, 2007)
This paper investigates the efficiency of household investment decisions using comprehensive disaggregated Swedish data. We consider two main sources of inefficiency: underdiversification ("down") and nonparticipation in risky asset markets ("out"). While a few households are very poorly diversified, most Swedish households outperform the Sharpe ratio of their domestic stock index through international diversification. Financially sophisticated households invest more efficiently but also more aggressively, and overall they incur higher return losses from underdiversification. The return cost of nonparticipation is smaller by almost one-half when we take account of the fact that nonparticipants would likely be inefficient investors. (c) 2007 by The University of Chicago. All rights reserved.